In Utero Stem Cell and Gene Therapy: Current Status and Future Perspectives - Loukogeorgakis, Stavros P.; Flake, Alan W. (European Journal of Pediatric Surgery, 2014)
Advances in prenatal diagnosis have led to the development of fetal therapies for congenital disorders. Although in utero surgical intervention has been used successfully for correction of anatomical defects that cause fetal demise or long-term disability, its clinical indications remain limited. In contrast, prenatal stem cell and gene therapy might have tremendous potential to treat multiple inherited disorders, and could dramatically expand the use of fetal intervention to a wide range of anticipated pediatric and adult diseases. Despite encouraging results from studies in animal models of disease, the clinical utility of such therapies has been restricted by poor efficacy and concerns about safety. The aim of this review is to summarize experimental progress toward clinical application of in utero stem cell transplantation and gene transfer for the treatment of congenital disease.
Keywords: prenatal treatment; fetal therapy; stem cell transplantation; gene therapy